Revitalizing Traditional Astronomical Instruments: Developing a Local Dial Model for Accurate Prayer Time Determination - Sartika, Sartika; Salam, Hisbullah; Mansyur, Fakhruddin; M, Nurhidaya (Al-Hilal: Journal of Islamic Astronomy, 2025)
This study addresses the limitations of contemporary prayer time instruments, which often require complex calculations, electricity, internet connectivity, or direct exposure to sunlight, by developing a practical, local dial–based tool for community use. Employing a Research and Development (R&D) approach, data were collected through observation and documentation and analyzed using descriptive and comparative methods. The device integrates calculations from the Indonesian Ministry of Religious Affairs, including altitude corrections for Maghrib, Isha, and Fajr, processed through VBA in Microsoft Excel using astronomical formulas from Jean Meeus’s Astronomical Algorithms. The instrument comprises a dial field, support field, tripod, thread, spirit level, minute-scale ruler, and stick, with the dial incorporating an analog prayer-time circle, an ‘Asr curve, and a Zuhr line. Comparative testing against the official prayer schedule demonstrates high accuracy with only a one-minute deviation. Designed for long-term use, the device remains valid for 50 years from 2023 and is applicable within a 27.5 km radius of Universitas Muhammadiyah Makassar.